Association of BDNF levels with IQ: comparison of S100B and BDNF levels in typically developing children and subjects with neurologically normal nonsyndromic intellectual disability - Esnafoglu, E.; Adıgüzel, Ö. (Journal of intellectual disability research, 2021)
Background Brain‐derived neurotrophic factor (BDNF) and S100B are reported to play an important role in neurodevelopment and may contribute to developmental pathogenesis in neuropsychiatric diseases. In this study, we aimed to examine the possible roles of BDNF and S100B in the pathogenesis of nonsyndromic intellectual disability (NS‐ID) and their relationship with cognitive performance. Methods Thirty‐three patients with intellectual disability (ID) and 30 typically developing children were compared. BDNF and S100B serum levels were measured with ELISA. The Wechsler Intelligence Scale for Children‐Revised Short form (WISC‐R) and Leiter intelligence test were administered to determine the intelligence levels of subjects. Leiter intelligence test was applied to 10 participants (30.31%) in the ID group because they had speech and communication problems. All other participants underwent WISC‐R. Results Brain‐derived neurotrophic factor levels were found to be significantly low in the patient group (mean ± SD, 67.43 ± 29.74 pg/mL) compared with the control group (94.67 ± 32.55 pg/mL) (P = 0.002). When S100B is assessed, there was no significant difference found between the patient group (335.05 ± 279.89 pg/mL) and control group (295.30 ± 146.55 pg/mL) (P = 0.901). There was a significant positive correlation between BDNF and performance IQ (r = 0.424 and P = 0.001) in all participants. In addition, positive correlations were found between BDNF levels and initiating speech time (r = −0.369 and P = 0.003). Conclusions Brain‐derived neurotrophic factor deficiency is proposed to have a possible role in the pathology of NS‐ID. High BDNF levels may be associated with better cognitive performance.